Flexionsmarker der zweiten Person Singular aus diachroner und synchroner Sicht. Vom germanischen zum althochdeutschen Zustand. - Woźnicka, Marta (Studia Germanica Posnaniensia, 2018)
Flexion elements are a typical feature of the so-called flexion languages and are characterized by the fact that they change their form depending on (in-)flexion and they decode at least two functions. In the case of a Germanic verb inflexion elements stand for two categories: person and a singular/ plural form. In Proto-Indo-European and Proto-Germanic the inflection elements were relatively independent and it was easy to separate them from a verb stem which consisted of the so-called root and other components such as tense or mode markers. In old Germanic languages the processes of fusion and creating portmanteau word(s) (language contamination so to speak) were so advanced that it is difficult, yet not impossible, to separate primary flexion elements. The article presents the development of the 2-nd person singular marker from the Germanic state with regard to the Gothic language up to the old-high-German phase. The markers which were analysed belonged to the Present and Past Tense paradigm of all modes of the selected verb groups, that is both weak and strong ones and the rest not belonging to any of the groups mentioned above. The flexion elements were identified using a synchronic model of a morphological description worked out by Józef Darski (1987, 22004). Modification of the model concerning the character of diachronic studies ensures alsoa proper historical description.